A corrosion-resistant preparation process for stainless steel used in extreme working conditions
By spraying paints containing aluminum dihydrogen phosphate, silicon sol, molybdenum oxide and other coatings on the surface of the stainless steel, and adding cobalt tungstate nanofibers, a corrosion-resistant coating is formed after heat treatment, the corrosion-resistant stainless steel is solved in the high-temperature molten salt environment, and the safety, environmental protection, corrosion resistance and service life are improved.
Patent Information
- Application Number
- CN202510126095.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-27
AI Technical Summary
Existing stainless steel materials are prone to corrosion in high-temperature molten salt environments, resulting in a shortened service life of the equipment and an increased maintenance cost. The existing anti-corrosion coatings have problems such as high cost, long construction cycle and poor density.
A coating process is adopted, and the coating composition includes 10~30 wt% aluminum dihydrogen phosphate, 5~10 wt% silicon sol, 1~5 wt% molybdenum oxide, 0.1~1.0 wt% carboxymethylcellulose, 0.1~1.0 wt% polyvinyl alcohol, cobalt tungstate nanofibers are added as corrosion-resistant aggregate, and a corrosion-resistant coating is formed by spraying and heat treatment at 500~700°C for 5 hours.
This coating significantly improves the corrosion resistance of stainless steel under high temperature molten salt environment, has a service life of more than 5,000 hours, is chromium-free, safe and environmentally friendly, and replaces traditional chromium-containing coating processes.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel surface treatment, and in particular to a corrosion-resistant preparation process for stainless steel used under extreme working conditions. Background Art
[0002] Stainless steel, which complies with ASME standards, has been widely adopted in high-temperature applications such as nuclear energy, thermal power generation, aviation and aerospace due to its significant cost-effectiveness. The material exhibits excellent corrosion resistance in a variety of aqueous solutions and high-temperature oxidizing environments, and a chromium-rich passivation film or oxide film can be formed on its surface. These surface films provide effective protection for the alloy matrix and can inhibit further corrosion of the alloy, thereby giving the material excellent high-temperature stability and corrosion resistance. Therefore, stainless steel is widely used in high-temperature heating furnaces in heat treatment processes and molten salt storage tanks and other equipment.
[0003] In the process of producing silicon steel sheets, a series of delicate processes are required. First, the rolled silicon steel sheets must go through steps such as pickling and alkali washing to ensure the cleanliness of their surfaces. These cleaning processes are essential for removing impurities and oil stains on the surface of the silicon steel sheets. After cleaning, the silicon steel sheets need to enter a high-temperature heating furnace for drying. During the drying process, the high-temperature water vapor and the molten salt produced during the alkali washing process will cause serious corrosion problems to the metal components in the kiln, especially the stainless steel components. This corrosion will not only affect the service life of the kiln, but may also lead to a decrease in production efficiency and an increase in maintenance costs.
[0004] Molten salt is the most important heat transfer and storage material in solar thermal power generation systems. It has high storage temperature and long storage time. However, chromium, an important alloying element for stainless steel to improve its corrosion resistance, is thermodynamically unstable in nitrate molten salt and / or chloride molten salt systems. It will not form a protective surface film and is prone to continuous corrosion. Most commercial stainless steel materials with reasonable prices will suffer from relatively serious corrosion damage when used in medium and high temperature molten salts for a long time, and cannot meet the goal of 30-year material life.
[0005] At present, there are two main methods to improve the performance of stainless steel: one is to regulate the composition of alloy elements; the other is to modify the surface of the material. Obviously, the first method is not applicable when the alloy composition has been determined, and regulating the alloy composition requires a lot of experimental support, which is time-consuming. The second method can mainly achieve the purpose of improving the performance of the material by changing the surface properties of the material without changing the structural design. In the existing market, high-temperature corrosion protection coatings for high-temperature furnaces, molten salt storage tanks, etc. are mainly coated on the surface of the substrate by thermal spraying. A layer of nickel-chromium-titanium alloy can play a certain protective effect on the stainless steel substrate in a short time. However, in the long-term corrosion test process, it was found that the metal elements between the coating and the substrate would undergo serious mutual diffusion, and a large number of cracks would appear in the coating. There are also defects such as high cost, long construction period, and poor density. Summary of the invention
[0006] The purpose of the present invention is to provide a corrosion-resistant preparation process for stainless steel used under extreme working conditions to solve the problems existing in the prior art.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a corrosion-resistant preparation process of stainless steel used in extreme working conditions, wherein the preparation process is:
[0008] (1) Cleaning of substrate;
[0009] (2) spraying a coating onto the cleaned substrate, drying at room temperature for 24 hours after spraying, and heat treating the substrate at 500-700° C. in a muffle furnace for 5 hours; the coating comprises 10-30 wt % of aluminum dihydrogen phosphate, 5-10 wt % of silica sol, 1-5 wt % of molybdenum oxide, 0.1-1.0 wt % of carboxymethyl cellulose, 0.1-1.0 wt % of polyvinyl alcohol, and the remainder is water.
[0010] The present invention uses molybdenum oxide as a curing agent, which can undergo a substitution reaction with hydrogen in phosphate to generate irregular compounds, release heat, and promote the coating to undergo a curing film-forming reaction at room temperature, which is different from the traditional coating that needs to be cured at a temperature of 150°C or higher. The coating of the present invention has better promotion significance and can also improve the water resistance and wear resistance of the film layer.
[0011] Furthermore, the substrate in step (1) is stainless steel, including one or more of austenitic stainless steel, ferritic stainless steel, austenitic-ferritic duplex stainless steel, martensitic stainless steel and precipitation hardening stainless steel.
[0012] Furthermore, the austenitic stainless steel includes one or more of 316 stainless steel, 316L stainless steel, 304 stainless steel and 304L stainless steel.
[0013] Furthermore, in step (1), the cleaning is performed by blowing the surface with dry hot air at 30-35°C or unheated air.
[0014] Furthermore, the coating also includes cobalt tungstate nanofibers, and the solid content of the cobalt tungstate nanofibers in the coating is 30-45wt%.
[0015] Furthermore, the preparation method of the cobalt tungstate nanofiber is as follows: sodium tungstate, cobalt nitrate and polyvinyl pyrrolidone are used as reaction raw materials to prepare a spinnable precursor sol, which is obtained after electrostatic spinning and calcination, and has a diameter of 100-400nm and a length of 5-20μm.
[0016] The present invention adds cobalt tungstate nanofibers as anti-corrosion aggregates. Since phosphates and Fe in steel can react to form stable compounds such as iron phosphate and ferrous phosphate, when in service at high temperatures, metal elements (Cr, Fe) will diffuse into the coating to enhance the adhesion between the substrate and the coating. The element concentration gradient caused by the diffusion will improve the CTE matching. At this time, the nano cobalt tungstate fibers will form a network structure as the skeleton inside the coating, improving the density and toughness of the coating. The relatively high external Co spinel layer is inert in molten salts and can effectively resist corrosion. Since there is no Cr in the CoWO4 nanofibers, 3+ Diffusion provides a place for Cr to gather under the cobalt tungstate nanonetwork to form a continuous Cr-rich oxide layer, which effectively inhibits the internal oxidation of the matrix, resulting in a small number of defects in the matrix. Therefore, the coating prepared by the present invention has a good protective effect on the corrosion of steel during high-temperature service, and can alleviate corrosion by inhibiting the diffusion of oxidizing ions in the molten salt into the stainless steel matrix and reducing the diffusion and loss of metal ions in the matrix.
[0017] Furthermore, the coating also includes aluminum sol, and the aluminum sol accounts for 5-10wt% of the coating.
[0018] Furthermore, the average particle size of the silica sol is 10 nm, and the pH value is 2-3; the average particle size of the aluminum sol is 5 nm.
[0019] The present invention adds silica sol to phosphate coating to modify it, which can improve the surface quality of the cured coating, reduce the curing temperature of the coating, and improve the corrosion resistance of the coating. Silica sol is a nano-scale SiO 2 The emulsion formed by particles dispersed in water or other solvents contains a large amount of water and active groups such as hydroxyl groups on its surface, which can form a network structure with phosphate through active hydroxyl groups to improve the stability of the coating. At the same time, silica sol can form a film at room temperature, and the formed film layer can be used as the nucleation center of phosphate curing crystallization, reducing the energy required for coating curing and lowering its curing temperature.
[0020] The present invention adds small-particle aluminum sol, and the surface area of nanoparticles with small particle size is large, and the adhesion on the substrate material is strong, thereby improving the bonding force between the coating and the stainless steel material. Therefore, the present invention does not need to perform pre-treatment processes such as sandblasting on the stainless steel material before preparing the coating, which greatly reduces the production cost. The aluminum sol used in the present invention is mixed with the silica sol for particle size adjustment, and the nano silicon oxide with a small particle size is compounded with the aluminum oxide with a smaller particle size to achieve densification of the coating, and at the same time, it can better combine with phosphate, and the aluminum oxide has a certain hydrophobicity, which can avoid the rust problem caused by the hygroscopicity of free phosphorus after the coating is sintered.
[0021] Furthermore, during the spraying, the distance between the nozzle of the spraying device and the surface of the substrate is 10-20 cm, and the spraying pressure is 3-6 kgf / cm 2 .
[0022] Furthermore, the coating amount on the substrate surface is 0.5-6.0 g / m 2 .
[0023] Furthermore, the preparation method of the coating is: grind the cobalt tungstate and pass it through a 325 mesh sieve, add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate, and continue stirring at 100-150rpm before spraying.
[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0025] The coating material of the present invention is different from the conventional coating and does not contain chromium anhydride or chromate. 6+ The composition is harmless to the human body and the environment, safe and environmentally friendly, and solves the hazards caused by the chromium element. The coating preparation process is simple to operate, and there are no special requirements when applied to stainless steel. It can completely replace the existing chromium-containing coating process, and compared with traditional chromium-containing coatings, it has a better protective effect on the corrosion of stainless steel in a molten salt environment, and the service life is greater than 5000 hours. The present invention can alleviate the corrosion by inhibiting the diffusion of oxidizing ions in the molten salt into the stainless steel matrix and reducing the diffusion and loss of metal ions in the matrix.
[0026] The chromium-free coating prepared by the present invention is not only safe and environmentally friendly, but also has excellent adhesion and corrosion resistance characteristics, is suitable for stainless steel, and can also be further used on other steel materials and alloys. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] A corrosion-resistant coating for stainless steel, comprising 10wt% aluminum dihydrogen phosphate, 5wt% silica sol, 5wt% aluminum sol, 1wt% molybdenum oxide, 0.1wt% carboxymethyl cellulose, 0.1wt% polyvinyl alcohol, and the rest being water;
[0030] The preparation method of the coating is:
[0031] (1) 0.8 g sodium tungstate and 0.5 g cobalt nitrate were dissolved in a mixed solvent consisting of 3 mL methanol and 7 mL N,N-dimethylformamide, stirred until completely dissolved, and 0.86 g polyvinyl pyrrolidone was added and stirred evenly to obtain a spinnable precursor sol with a viscosity of 0.5 Pa·S; the spinnable precursor sol was sprayed onto a receiving plate using a plastic syringe with a stainless steel needle, the receiving distance between the stainless steel needle of the syringe and the receiving plate was 15 cm, the ejection rate of the spinnable precursor sol was 1.5 mL / h, the voltage was 20 kV, and the electrospinning temperature was controlled at 25°C to obtain a precursor fiber; the precursor fiber was dried in a drying oven at 60°C for 12 h, and then placed in a high-temperature furnace, heated to 550°C at a heating rate of 2°C / min, and kept warm for 120 min to obtain cobalt tungstate nanofibers with a diameter of 250 nm and a length of 10 μm;
[0032] (2) Adding ethanol to a sodium hydroxide aqueous solution having a mass percentage concentration of 5% to make its mass percentage concentration of 0.5% to obtain an alkaline solution; washing nano-scale silicon powder with lactic acid, washing with deionized water until the pH is 6.5, taking 200 kg of silicon powder, adding it to the alkaline solution at a rate of 20 kg / h, stirring and reacting at 50° C. for 10 hours, dynamically monitoring until the silicon content in the reaction solution remains unchanged as the reaction end point, filtering to obtain a small-particle silica sol dilute solution; adding diatomaceous earth as an adsorbent to the small-particle silica sol dilute solution, filtering with a precision filter to remove the pigment and dispersant in the silica sol solution, and then reducing the pressure to concentrate, the concentration end point is that the solid content of the silica sol aqueous solution is 25%, and the average particle size is 10 nm, and then adjusting the sol pH to 3 with acetic acid having a mass percentage concentration of 30% to obtain silica sol;
[0033] (3) Add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate nanofibers to a solid content of 30wt%, and continue stirring at 150rpm until before spraying; wherein, aluminum sol is an alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0034] The coating prepared in this embodiment is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2 , dried at room temperature for 24 hours, and then placed in a muffle furnace for heat treatment at 700° C. for 5 hours. The coating prepared in this embodiment is smooth and complete.
[0035] The coating prepared by the coating of this embodiment was tested for adhesion according to GB / T2522-2007, and the coating had good adhesion. The hardness of the coating was determined according to the method of GB / T6739-2006, and the hardness was higher than 5H.
[0036] Example 2
[0037] A corrosion-resistant coating for stainless steel, comprising 20wt% aluminum dihydrogen phosphate, 5wt% silica sol, 5wt% aluminum sol, 3wt% molybdenum oxide, 0.6wt% carboxymethyl cellulose, 0.6wt% polyvinyl alcohol, and the rest being water;
[0038] The preparation method of the coating is:
[0039] (1) 0.8 g sodium tungstate and 0.5 g cobalt nitrate were dissolved in a mixed solvent consisting of 3 mL methanol and 7 mL N,N-dimethylformamide, stirred until completely dissolved, and 0.86 g polyvinyl pyrrolidone was added and stirred evenly to obtain a spinnable precursor sol with a viscosity of 0.5 Pa·S; the spinnable precursor sol was sprayed onto a receiving plate using a plastic syringe with a stainless steel needle, the receiving distance between the stainless steel needle of the syringe and the receiving plate was 15 cm, the ejection rate of the spinnable precursor sol was 1.5 mL / h, the voltage was 20 kV, and the electrospinning temperature was controlled at 25°C to obtain a precursor fiber; the precursor fiber was dried in a drying oven at 60°C for 12 h, and then placed in a high-temperature furnace, heated to 550°C at a heating rate of 2°C / min, and kept warm for 120 min to obtain cobalt tungstate nanofibers with a diameter of 250 nm and a length of 10 μm;
[0040] (2) Adding ethanol to a sodium hydroxide aqueous solution having a mass percentage concentration of 5% to make its mass percentage concentration of 0.5% to obtain an alkaline solution; washing nano-scale silicon powder with lactic acid, washing with deionized water until the pH is 6.5, taking 200 kg of silicon powder, adding it to the alkaline solution at a rate of 20 kg / h, stirring and reacting at 50° C. for 10 hours, dynamically monitoring until the silicon content in the reaction solution remains unchanged as the reaction end point, filtering to obtain a small-particle silica sol dilute solution; adding diatomaceous earth as an adsorbent to the small-particle silica sol dilute solution, filtering with a precision filter to remove the pigment and dispersant in the silica sol solution, and then reducing the pressure to concentrate, the concentration end point is that the solid content of the silica sol aqueous solution is 25%, and the average particle size is 10 nm, and then adjusting the sol pH to 3 with acetic acid having a mass percentage concentration of 30% to obtain silica sol;
[0041] (3) Add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate nanofibers to a solid content of 40wt%, and continue stirring at 150rpm until before spraying; wherein, aluminum sol is an alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0042] The coating prepared in this embodiment is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2 , dried at room temperature for 24 hours, and then placed in a muffle furnace for heat treatment at 700° C. for 5 hours. The coating prepared in this embodiment is smooth and complete.
[0043] The coating obtained by using the coating prepared in this embodiment was tested for coating adhesion according to GB / T2522-2007, and the coating adhesion was good; the hardness of the coating was determined according to the method of GB / T6739-2006, and the hardness was higher than 7H.
[0044] Example 3
[0045] A corrosion-resistant coating for stainless steel comprises 15wt% of aluminum dihydrogen phosphate, 6wt% of silica sol, 5wt% of aluminum sol, 2wt% of molybdenum oxide, 0.3wt% of carboxymethyl cellulose, 0.3wt% of polyvinyl alcohol, and the remainder is water.
[0046] The preparation method of the coating is:
[0047] (1) 0.8 g sodium tungstate and 0.5 g cobalt nitrate were dissolved in a mixed solvent consisting of 3 mL methanol and 7 mL N,N-dimethylformamide, stirred until completely dissolved, and 0.86 g polyvinyl pyrrolidone was added and stirred evenly to obtain a spinnable precursor sol with a viscosity of 0.5 Pa·S; the spinnable precursor sol was sprayed onto a receiving plate using a plastic syringe with a stainless steel needle, the receiving distance between the stainless steel needle of the syringe and the receiving plate was 15 cm, the ejection rate of the spinnable precursor sol was 1.5 mL / h, the voltage was 20 kV, and the electrospinning temperature was controlled at 25°C to obtain a precursor fiber; the precursor fiber was dried in a drying oven at 60°C for 12 h, and then placed in a high-temperature furnace, heated to 550°C at a heating rate of 2°C / min, and kept warm for 120 min to obtain cobalt tungstate nanofibers with a diameter of 250 nm and a length of 10 μm;
[0048] (2) Adding ethanol to a sodium hydroxide aqueous solution having a mass percentage concentration of 5% to make its mass percentage concentration of 0.5% to obtain an alkaline solution; washing nano-scale silicon powder with lactic acid, washing with deionized water until the pH is 6.5, taking 200 kg of silicon powder, adding it to the alkaline solution at a rate of 20 kg / h, stirring and reacting at 50° C. for 10 hours, dynamically monitoring until the silicon content in the reaction solution remains unchanged as the reaction end point, filtering to obtain a small-particle silica sol dilute solution; adding diatomaceous earth as an adsorbent to the small-particle silica sol dilute solution, filtering with a precision filter to remove the pigment and dispersant in the silica sol solution, and then reducing the pressure to concentrate, the concentration end point is that the solid content of the silica sol aqueous solution is 25%, and the average particle size is 10 nm, and then adjusting the sol pH to 3 with acetic acid having a mass percentage concentration of 30% to obtain silica sol;
[0049] (3) Add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate nanofibers to a solid content of 34wt%, and continue stirring at 150rpm until before spraying; wherein, aluminum sol is an alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0050] The coating prepared in this embodiment is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2 , dried at room temperature for 24 hours, and then placed in a muffle furnace for heat treatment at 700° C. for 5 hours. The coating prepared in this embodiment is smooth and complete.
[0051] The coating prepared by the coating of this embodiment was tested for adhesion according to GB / T2522-2007, and the coating had good adhesion. The hardness of the coating was determined according to the method of GB / T6739-2006, and the hardness was higher than 6H.
[0052] Example 4
[0053] A corrosion-resistant coating for stainless steel, comprising 20wt% aluminum dihydrogen phosphate, 7.5wt% silica sol, 5wt% aluminum sol, 3wt% molybdenum oxide, 0.5wt% carboxymethyl cellulose, 0.5wt% polyvinyl alcohol, and the rest being water;
[0054] The preparation method of the coating is:
[0055] (1) 0.8 g sodium tungstate and 0.5 g cobalt nitrate were dissolved in a mixed solvent consisting of 3 mL methanol and 7 mL N,N-dimethylformamide, stirred until completely dissolved, and 0.86 g polyvinyl pyrrolidone was added and stirred evenly to obtain a spinnable precursor sol with a viscosity of 0.5 Pa·S; the spinnable precursor sol was sprayed onto a receiving plate using a plastic syringe with a stainless steel needle, the receiving distance between the stainless steel needle of the syringe and the receiving plate was 15 cm, the ejection rate of the spinnable precursor sol was 1.5 mL / h, the voltage was 20 kV, and the electrospinning temperature was controlled at 25°C to obtain a precursor fiber; the precursor fiber was dried in a drying oven at 60°C for 12 h, and then placed in a high-temperature furnace, heated to 550°C at a heating rate of 2°C / min, and kept warm for 120 min to obtain cobalt tungstate nanofibers with a diameter of 250 nm and a length of 10 μm;
[0056] (2) Adding ethanol to a sodium hydroxide aqueous solution having a mass percentage concentration of 5% to make its mass percentage concentration of 0.5% to obtain an alkaline solution; washing nano-scale silicon powder with lactic acid, washing with deionized water until the pH is 6.5, taking 200 kg of silicon powder, adding it to the alkaline solution at a rate of 20 kg / h, stirring and reacting at 50° C. for 10 hours, dynamically monitoring until the silicon content in the reaction solution remains unchanged as the reaction end point, filtering to obtain a small-particle silica sol dilute solution; adding diatomaceous earth as an adsorbent to the small-particle silica sol dilute solution, filtering with a precision filter to remove the pigment and dispersant in the silica sol solution, and then reducing the pressure to concentrate, the concentration end point is that the solid content of the silica sol aqueous solution is 25%, and the average particle size is 10 nm, and then adjusting the sol pH to 3 with acetic acid having a mass percentage concentration of 30% to obtain silica sol;
[0057] (3) Add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate nanofibers to a solid content of 37wt%, and continue stirring at 150rpm until before spraying; wherein, aluminum sol is an alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0058] The coating prepared in this embodiment is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2, dried at room temperature for 24 hours, and then placed in a muffle furnace for heat treatment at 700° C. for 5 hours. The coating prepared in this embodiment is smooth and complete.
[0059] The coating obtained by using the coating prepared in this embodiment was tested for coating adhesion according to GB / T2522-2007, and the coating adhesion was good; the hardness of the coating was determined according to the method of GB / T6739-2006, and the hardness was higher than 7H.
[0060] Example 5
[0061] A corrosion-resistant coating for stainless steel, comprising 25wt% aluminum dihydrogen phosphate, 8wt% silica sol, 6.5wt% aluminum sol, 4wt% molybdenum oxide, 0.7wt% carboxymethyl cellulose, 0.7wt% polyvinyl alcohol, and the rest is water;
[0062] The preparation method of the coating is:
[0063] (1) 0.8 g sodium tungstate and 0.5 g cobalt nitrate were dissolved in a mixed solvent consisting of 3 mL methanol and 7 mL N,N-dimethylformamide, stirred until completely dissolved, and 0.86 g polyvinyl pyrrolidone was added and stirred evenly to obtain a spinnable precursor sol with a viscosity of 0.5 Pa·S; the spinnable precursor sol was sprayed onto a receiving plate using a plastic syringe with a stainless steel needle, the receiving distance between the stainless steel needle of the syringe and the receiving plate was 15 cm, the ejection rate of the spinnable precursor sol was 1.5 mL / h, the voltage was 20 kV, and the electrospinning temperature was controlled at 25°C to obtain a precursor fiber; the precursor fiber was dried in a drying oven at 60°C for 12 h, and then placed in a high-temperature furnace, heated to 550°C at a heating rate of 2°C / min, and kept warm for 120 min to obtain cobalt tungstate nanofibers with a diameter of 250 nm and a length of 10 μm;
[0064] (2) Adding ethanol to a sodium hydroxide aqueous solution having a mass percentage concentration of 5% to make its mass percentage concentration of 0.5% to obtain an alkaline solution; washing nano-scale silicon powder with lactic acid, washing with deionized water until the pH is 6.5, taking 200 kg of silicon powder, adding it to the alkaline solution at a rate of 20 kg / h, stirring and reacting at 50° C. for 10 hours, dynamically monitoring until the silicon content in the reaction solution remains unchanged as the reaction end point, filtering to obtain a small-particle silica sol dilute solution; adding diatomaceous earth as an adsorbent to the small-particle silica sol dilute solution, filtering with a precision filter to remove the pigment and dispersant in the silica sol solution, and then reducing the pressure to concentrate, the concentration end point is that the solid content of the silica sol aqueous solution is 25%, and the average particle size is 10 nm, and then adjusting the sol pH to 3 with acetic acid having a mass percentage concentration of 30% to obtain silica sol;
[0065] (3) Add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate nanofibers to a solid content of 41wt%, and continue stirring at 150rpm until before spraying; wherein, aluminum sol is an alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0066] The coating prepared in this embodiment is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2 , dried at room temperature for 24 hours, and then placed in a muffle furnace for heat treatment at 700° C. for 5 hours. The coating prepared in this embodiment is smooth and complete.
[0067] The coating obtained by using the coating prepared in this embodiment was tested for coating adhesion according to GB / T2522-2007, and the coating adhesion was good; the hardness of the coating was determined according to the method of GB / T6739-2006, and the hardness was higher than 7H.
[0068] Example 6
[0069] A corrosion-resistant coating for stainless steel, comprising 30wt% aluminum dihydrogen phosphate, 10wt% silica sol, 10wt% aluminum sol, 5wt% molybdenum oxide, 1.0wt% carboxymethyl cellulose, 1.0wt% polyvinyl alcohol, and the rest is water;
[0070] The preparation method of the coating is:
[0071] (1) 0.8 g sodium tungstate and 0.5 g cobalt nitrate were dissolved in a mixed solvent consisting of 3 mL methanol and 7 mL N,N-dimethylformamide, stirred until completely dissolved, and 0.86 g polyvinyl pyrrolidone was added and stirred evenly to obtain a spinnable precursor sol with a viscosity of 0.5 Pa·S; the spinnable precursor sol was sprayed onto a receiving plate using a plastic syringe with a stainless steel needle, the receiving distance between the stainless steel needle of the syringe and the receiving plate was 15 cm, the ejection rate of the spinnable precursor sol was 1.5 mL / h, the voltage was 20 kV, and the electrospinning temperature was controlled at 25°C to obtain a precursor fiber; the precursor fiber was dried in a drying oven at 60°C for 12 h, and then placed in a high-temperature furnace, heated to 550°C at a heating rate of 2°C / min, and kept warm for 120 min to obtain cobalt tungstate nanofibers with a diameter of 250 nm and a length of 10 μm;
[0072] (2) Adding ethanol to a sodium hydroxide aqueous solution having a mass percentage concentration of 5% to make its mass percentage concentration of 0.5% to obtain an alkaline solution; washing nano-scale silicon powder with lactic acid, washing with deionized water until the pH is 6.5, taking 200 kg of silicon powder, adding it to the alkaline solution at a rate of 20 kg / h, stirring and reacting at 50° C. for 10 hours, dynamically monitoring until the silicon content in the reaction solution remains unchanged as the reaction end point, filtering to obtain a small-particle silica sol dilute solution; adding diatomaceous earth as an adsorbent to the small-particle silica sol dilute solution, filtering with a precision filter to remove the pigment and dispersant in the silica sol solution, and then reducing the pressure to concentrate, the concentration end point is that the solid content of the silica sol aqueous solution is 25%, and the average particle size is 10 nm, and then adjusting the sol pH to 3 with acetic acid having a mass percentage concentration of 30% to obtain silica sol;
[0073] (3) Add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate nanofibers to a solid content of 45wt%, and continue stirring at 150rpm until before spraying; wherein, aluminum sol is an alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0074] The coating prepared in this embodiment is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2 , dried at room temperature for 24 hours, and then placed in a muffle furnace for heat treatment at 700° C. for 5 hours. The coating prepared in this embodiment is smooth and complete.
[0075] The coating obtained by using the coating prepared in this embodiment was tested for coating adhesion according to GB / T2522-2007, and the coating adhesion was good; the hardness of the coating was determined according to the method of GB / T6739-2006, and the hardness was higher than 7H.
[0076] Comparative Example 1
[0077] The difference between Comparative Example 1 and Example 2 is that no silica sol is added, and its components include 20wt% aluminum dihydrogen phosphate, 5wt% aluminum sol, 3wt% molybdenum oxide, 0.6wt% carboxymethyl cellulose, 0.6wt% polyvinyl alcohol, and the rest is water;
[0078] The preparation method of the coating is:
[0079] (1) 0.8 g sodium tungstate and 0.5 g cobalt nitrate were dissolved in a mixed solvent consisting of 3 mL methanol and 7 mL N,N-dimethylformamide, stirred until completely dissolved, and 0.86 g polyvinyl pyrrolidone was added and stirred evenly to obtain a spinnable precursor sol with a viscosity of 0.5 Pa·S; the spinnable precursor sol was sprayed onto a receiving plate using a plastic syringe with a stainless steel needle, the receiving distance between the stainless steel needle of the syringe and the receiving plate was 15 cm, the ejection rate of the spinnable precursor sol was 1.5 mL / h, the voltage was 20 kV, and the electrospinning temperature was controlled at 25°C to obtain a precursor fiber; the precursor fiber was dried in a drying oven at 60°C for 12 h, and then placed in a high-temperature furnace, heated to 550°C at a heating rate of 2°C / min, and kept warm for 120 min to obtain cobalt tungstate nanofibers with a diameter of 250 nm and a length of 10 μm;
[0080] (2) Add aluminum dihydrogen phosphate, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate nanofibers to a solid content of 40wt%, and continue stirring at 150rpm until before spraying; wherein, the aluminum sol is an alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0081] The coating prepared in this comparative example is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2 The coating curing time at room temperature is greater than 30 hours. After curing, it is placed in a muffle furnace and heat treated at 700°C for 5 hours.
[0082] The coating prepared by the coating of comparative example 1 was tested for adhesion according to GB / T2522-2007, and the coating adhesion was general, with partial shedding. The hardness of the coating was determined according to the method of GB / T6739-2006, and the hardness was higher than 5H.
[0083] Comparative Example 2
[0084] The difference between Comparative Example 2 and Example 2 is that no aluminum sol is added, and its components include 20wt% aluminum dihydrogen phosphate, 5wt% silica sol, 3wt% molybdenum oxide, 0.6wt% carboxymethyl cellulose, 0.6wt% polyvinyl alcohol, and the rest is water;
[0085] The preparation method of the coating is:
[0086] (1) 0.8 g sodium tungstate and 0.5 g cobalt nitrate were dissolved in a mixed solvent consisting of 3 mL methanol and 7 mL N,N-dimethylformamide, stirred until completely dissolved, and 0.86 g polyvinyl pyrrolidone was added and stirred evenly to obtain a spinnable precursor sol with a viscosity of 0.5 Pa·S; the spinnable precursor sol was sprayed onto a receiving plate using a plastic syringe with a stainless steel needle, the receiving distance between the stainless steel needle of the syringe and the receiving plate was 15 cm, the ejection rate of the spinnable precursor sol was 1.5 mL / h, the voltage was 20 kV, and the electrospinning temperature was controlled at 25°C to obtain a precursor fiber; the precursor fiber was dried in a drying oven at 60°C for 12 h, and then placed in a high-temperature furnace, heated to 550°C at a heating rate of 2°C / min, and kept warm for 120 min to obtain cobalt tungstate nanofibers with a diameter of 250 nm and a length of 10 μm;
[0087] (2) Adding ethanol to a sodium hydroxide aqueous solution having a mass percentage concentration of 5% to make its mass percentage concentration of 0.5% to obtain an alkaline solution; washing nano-scale silicon powder with lactic acid, washing with deionized water until the pH is 6.5, taking 200 kg of silicon powder, adding it to the alkaline solution at a rate of 20 kg / h, stirring and reacting at 50° C. for 10 hours, dynamically monitoring until the silicon content in the reaction solution remains unchanged as the reaction end point, filtering to obtain a small-particle silica sol dilute solution; adding diatomaceous earth as an adsorbent to the small-particle silica sol dilute solution, filtering with a precision filter to remove the pigment and dispersant in the silica sol solution, and then reducing the pressure to concentrate, the concentration end point is that the solid content of the silica sol aqueous solution is 25%, and the average particle size is 10 nm, and then adjusting the sol pH to 3 with acetic acid having a mass percentage concentration of 30% to obtain silica sol;
[0088] (3) Add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate nanofibers to a solid content of 40wt%, and continue stirring at 150rpm until before spraying; wherein, aluminum sol is an alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0089] The coating prepared in this comparative example is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2 , dried at room temperature for 24 h, and then placed in a muffle furnace for heat treatment at 700 °C for 5 h.
[0090] The coating prepared by the coating of this comparative example was tested for adhesion according to GB / T2522-2007, and the coating adhesion was general, with partial shedding. The hardness of the coating was determined according to the method of GB / T6739-2006, and the hardness was higher than 5H.
[0091] Comparative Example 3
[0092] The difference between Comparative Example 3 and Example 2 is that molybdenum oxide is not added, and its components include 20wt% aluminum dihydrogen phosphate, 5wt% silica sol, 5wt% aluminum sol, 0.6wt% carboxymethyl cellulose, 0.6wt% polyvinyl alcohol, and the rest is water;
[0093] The preparation method of the coating is:
[0094] (1) 0.8 g sodium tungstate and 0.5 g cobalt nitrate were dissolved in a mixed solvent consisting of 3 mL methanol and 7 mL N,N-dimethylformamide, stirred until completely dissolved, and 0.86 g polyvinyl pyrrolidone was added and stirred evenly to obtain a spinnable precursor sol with a viscosity of 0.5 Pa·S; the spinnable precursor sol was sprayed onto a receiving plate using a plastic syringe with a stainless steel needle, the receiving distance between the stainless steel needle of the syringe and the receiving plate was 15 cm, the ejection rate of the spinnable precursor sol was 1.5 mL / h, the voltage was 20 kV, and the electrospinning temperature was controlled at 25°C to obtain a precursor fiber; the precursor fiber was dried in a drying oven at 60°C for 12 h, and then placed in a high-temperature furnace, heated to 550°C at a heating rate of 2°C / min, and kept warm for 120 min to obtain cobalt tungstate nanofibers with a diameter of 250 nm and a length of 10 μm;
[0095] (2) Adding ethanol to a sodium hydroxide aqueous solution having a mass percentage concentration of 5% to make its mass percentage concentration of 0.5% to obtain an alkaline solution; washing nano-scale silicon powder with lactic acid, washing with deionized water until the pH is 6.5, taking 200 kg of silicon powder, adding it to the alkaline solution at a rate of 20 kg / h, stirring and reacting at 50° C. for 10 hours, dynamically monitoring until the silicon content in the reaction solution remains unchanged as the reaction end point, filtering to obtain a small-particle silica sol dilute solution; adding diatomaceous earth as an adsorbent to the small-particle silica sol dilute solution, filtering with a precision filter to remove the pigment and dispersant in the silica sol solution, and then reducing the pressure to concentrate, the concentration end point is that the solid content of the silica sol aqueous solution is 25%, and the average particle size is 10 nm, and then adjusting the sol pH to 3 with acetic acid having a mass percentage concentration of 30% to obtain silica sol;
[0096] (3) Add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate nanofibers to a solid content of 40wt%, and continue stirring at 150rpm until before spraying; wherein, aluminum sol is an alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0097] The coating prepared in this comparative example is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2, it cannot be dried and solidified at room temperature, and needs to be dried at 120°C for 24 hours, and then placed in a muffle furnace for heat treatment at 700°C for 5 hours. The coating prepared in this embodiment is smooth and complete.
[0098] The coating prepared by the coating of this comparative example was tested for adhesion according to GB / T2522-2007, and the coating adhesion was general, with partial shedding. The hardness of the coating was determined according to the method of GB / T6739-2006, and the hardness was higher than 6H.
[0099] Comparative Example 4
[0100] The difference between Comparative Example 4 and Example 2 is that no cobalt tungstate nanofibers are added, and its components include 20wt% aluminum dihydrogen phosphate, 5wt% silica sol, 5wt% aluminum sol, 3wt% molybdenum oxide, 0.6wt% carboxymethyl cellulose, 0.6wt% polyvinyl alcohol, and the rest is water;
[0101] The preparation method of the coating is:
[0102] (1) Adding ethanol to a sodium hydroxide aqueous solution having a mass percentage concentration of 5% to make its mass percentage concentration of 0.5% to obtain an alkaline solution; washing nano-scale silicon powder with lactic acid, washing with deionized water until the pH is 6.5, taking 200 kg of silicon powder, adding it to the alkaline solution at a rate of 20 kg / h, stirring and reacting at 50° C. for 10 hours, dynamically monitoring until the silicon content in the reaction solution remains unchanged as the reaction end point, filtering to obtain a small-particle silica sol dilute solution; adding diatomaceous earth as an adsorbent to the small-particle silica sol dilute solution, filtering with a precision filter to remove the pigment and dispersant in the silica sol solution, and then reducing the pressure to concentrate, the concentration end point is that the solid content of the silica sol aqueous solution is 25%, and the average particle size is 10 nm, and then adjusting the sol pH to 3 with acetic acid having a mass percentage concentration of 30% to obtain silica sol;
[0103] (2) Add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, and continue stirring at 150 rpm until before spraying; among them, aluminum sol is the alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0104] The coating prepared in this comparative example is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2 , dried at room temperature for 24 hours, and then placed in a muffle furnace for heat treatment at 700°C for 5 hours. The coating prepared in this comparative example is smooth and complete.
[0105] The coating obtained by using the coating prepared in this comparative example is tested for coating adhesion according to GB / T2522-2007, and the coating adhesion is good; the hardness of the coating is determined according to the method of GB / T6739-2006, and the hardness is higher than 5H.
[0106] Comparative Example 5
[0107] The difference between Comparative Example 5 and Example 2 is that cobalt tungstate nanopowder of equal diameter replaces cobalt tungstate nanofibers, and its components include 20wt% aluminum dihydrogen phosphate, 5wt% silica sol, 5wt% aluminum sol, 3wt% molybdenum oxide, 0.6wt% carboxymethyl cellulose, 0.6wt% polyvinyl alcohol, and the rest is water;
[0108] The preparation method of the coating is:
[0109] (1) Adding ethanol to a sodium hydroxide aqueous solution having a mass percentage concentration of 5% to make its mass percentage concentration of 0.5% to obtain an alkaline solution; washing nano-scale silicon powder with lactic acid, washing with deionized water until the pH is 6.5, taking 200 kg of silicon powder, adding it to the alkaline solution at a rate of 20 kg / h, stirring and reacting at 50° C. for 10 hours, dynamically monitoring until the silicon content in the reaction solution remains unchanged as the reaction end point, filtering to obtain a small-particle silica sol dilute solution; adding diatomaceous earth as an adsorbent to the small-particle silica sol dilute solution, filtering with a precision filter to remove the pigment and dispersant in the silica sol solution, and then reducing the pressure to concentrate, the concentration end point is that the solid content of the silica sol aqueous solution is 25%, and the average particle size is 10 nm, and then adjusting the sol pH to 3 with acetic acid having a mass percentage concentration of 30% to obtain silica sol;
[0110] (2) Add aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide in order according to the coating ratio, stir evenly, then add aluminum sol, stir evenly, add carboxymethyl cellulose and polyvinyl alcohol and stir until completely dissolved, then add cobalt tungstate nanopowder with a diameter of 250nm to a solid content of 40wt%, and continue stirring at 150rpm until before spraying; wherein, aluminum sol is an alumina sol product of Ningbo Jiwei Nano New Material Technology Co., Ltd.
[0111] The coating prepared in this comparative example is used by spraying the prepared coating on cleaned 316 stainless steel at a coating amount of 2.5 g / m 2 , dried at room temperature for 24 hours, and then placed in a muffle furnace for heat treatment at 700°C for 5 hours. The coating prepared in this comparative example is smooth and complete.
[0112] The coating obtained by using the coating prepared in this comparative example was tested for coating adhesion according to GB / T2522-2007, and the coating adhesion was good; the hardness of the coating was determined according to the method of GB / T6739-2006, and the hardness was higher than 6H.
[0113] Table 1 below shows the weight loss per unit area of 316L stainless steel protected by coatings of Examples 1 to 6 of the present invention and Comparative Examples 1 to 5 after being immersed in a 700° C. high temperature molten salt (a mixed medium of 53% potassium nitrate + 40% sodium nitrite + 7% sodium nitrate) environment for 50 hours.
[0114] Table 1
[0115] Weight loss per unit area (mg / cm2) Example 1 0.45 Example 2 0.40 Example 3 0.44 Example 4 0.42 Example 5 0.40 Example 6 0.41 Comparative Example 1 0.49 Comparative Example 2 0.52 Comparative Example 3 0.46 Comparative Example 4 3.4 Comparative Example 5 0.55
[0116] Table 2 below shows the weight loss per unit area of 316L stainless steel protected by the coatings of Examples 1 to 6 of the present invention and Comparative Examples 1 to 5 after being immersed in a 700° C. NaCl molten salt environment for 50 hours.
[0117] Table 2
[0118] Weight loss per unit area (mg / cm2) Example 1 0.49 Example 2 0.44 Example 3 0.46 Example 4 0.46 Example 5 0.45 Example 6 0.47 Comparative Example 1 0.53 Comparative Example 2 0.56 Comparative Example 3 0.50 Comparative Example 4 4.8 Comparative Example 5 0.62
[0119] The coating prepared by the present invention is not only safe and environmentally friendly, but also has excellent adhesion and corrosion resistance. At the same time, a curing film-forming reaction occurs at room temperature. The coating of the present invention has better promotion significance.
[0120] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A corrosion-resistant preparation process for stainless steel used in extreme working conditions, characterized in that: Its preparation process is: (1) Cleaning of substrate; (2) spraying a coating onto a clean substrate, drying at room temperature for 24 hours after spraying, and heat treating the substrate in a muffle furnace at 500-700°C for 5 hours after drying; the coating comprises 10-30wt% aluminum dihydrogen phosphate, 5-10wt% silica sol, 1-5wt% molybdenum oxide, 0.1-1.0wt% carboxymethyl cellulose, 0.1-1.0wt% polyvinyl alcohol, cobalt tungstate nanofibers, 5-10wt% aluminum sol, and the rest is water; the solid content of the cobalt tungstate nanofibers in the coating is 30-45wt%; The average particle size of the silica sol is 10nm, and the pH value is 2-3; the particle size of the aluminum sol is 3-5nm, and its effective content is 20%-25%; The preparation method of the cobalt tungstate nanofiber is as follows: sodium tungstate, cobalt nitrate and polyvinyl pyrrolidone are used as reaction raw materials to prepare a spinnable precursor sol, which is obtained after electrostatic spinning and calcination. The diameter of the cobalt tungstate nanofiber is 100-400nm and the length is 5-20μm.
2. The corrosion-resistant preparation process of stainless steel used in extreme working conditions according to claim 1 is characterized in that: The substrate in step (1) is stainless steel, including one or more of austenitic stainless steel, ferritic stainless steel, austenitic-ferritic duplex stainless steel, martensitic stainless steel and precipitation hardening stainless steel.
3. The corrosion-resistant preparation process of stainless steel used in extreme working conditions according to claim 2 is characterized in that: The austenitic stainless steel includes one or more of 316 stainless steel, 316L stainless steel, 304 stainless steel and 304L stainless steel.
4. The corrosion-resistant preparation process of stainless steel used in extreme working conditions according to claim 1 is characterized in that: In step (1), the cleaning is performed by blowing the surface with dry 30-35°C hot air or unheated air.
5. The corrosion-resistant preparation process of stainless steel used in extreme working conditions according to claim 1 is characterized in that: During the spraying, the distance between the nozzle of the spraying device and the surface of the substrate is 10-20 cm, and the spraying pressure is 3-6 kgf / cm 2 .
6. The corrosion-resistant preparation process of stainless steel used in extreme working conditions according to claim 1 is characterized in that: The coating amount on the substrate surface is 0.5-6.0 g / m 2 .
7. The corrosion-resistant preparation process of stainless steel used in extreme working conditions according to claim 1 is characterized in that: The preparation method of the coating is as follows: according to the coating ratio, aluminum dihydrogen phosphate, silica sol, water, and molybdenum oxide are added in sequence, stirred evenly, and then aluminum sol is added. After stirring evenly, carboxymethyl cellulose and polyvinyl alcohol are added and stirred until completely dissolved, and then cobalt tungstate nanofibers are added, and stirring is continued at 100-150 rpm before spraying.
Citation Information
Patent Citations
Surface treatment agent for aluminum-containing metal material
CN116997678A